2013
DOI: 10.4149/endo_2013_01_33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome, insulin resistance, and microvascular angina pectoris in 500 consecutive patients referred to coronarography

Abstract: Hyperinsulinemia and high prevalence of various symptoms of metabolic syndrome (MS) were found in high percentage of patients with after load precordial pain who were referred to coronarography. Similarly, in several women, MIV-AP was detected and its affiliation to MS suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Human MetS has been associated with an increased risk of CVD such as myocardial infarction, stroke [40], and coronary microvascular dysfunction linked to a microvascular form of angina pectoris [11]. Microvascular dysfunction is reported to be associated with poor cardiovascular outcomes [41,42], including left ventricular remodeling [43].…”
Section: Discussionmentioning
confidence: 99%
“…Human MetS has been associated with an increased risk of CVD such as myocardial infarction, stroke [40], and coronary microvascular dysfunction linked to a microvascular form of angina pectoris [11]. Microvascular dysfunction is reported to be associated with poor cardiovascular outcomes [41,42], including left ventricular remodeling [43].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is mainly secreted from stromal vascular cells [ 46 ]. Elevated IL-6 plasma levels have been described in patients with T2D and especially in those who had features of insulin resistance [ 47 ]. These levels declined in parallel with weight loss in obese individuals undergoing bariatric surgery [ 48 ].…”
Section: Adipokines and Other Molecules That May Induce Insulin Resismentioning
confidence: 99%
“…Its pathological mechanism is mainly related to the disorder of glucose and lipid metabolism of cardiomyocytes under high glucose environment, and the electrophysiological abnormalities of cardiomyocytes caused by changes in energy metabolism. Hrnciar [35] found that 74.3% of patients with macrovascular lesions of coronary artery disease had insulin resistance. In addition, adipocytes in patients with type 2 diabetes also show insulin resistance, with continuous fat dissolution, elevated free fatty acids and transported to the liver, resulting in increased liver derived very low-density lipoprotein cholesterol, which eventually leads to the aggravation of atherosclerosis [36] .…”
Section: Insulin Resistancementioning
confidence: 99%